Theoretical and kinetic modeling study of chloromethane (CH3Cl) pyrolysis and oxidation. Issue 3 (5th November 2020) - Pelucchi, Matteo; Cavallotti, Carlo; Frassoldati, Alessio; Ranzi, Eliseo; Glarborg, Peter; Faravelli, Tiziano
Abstract: This work presents a comprehensive kinetic modeling study of the pyrolysis and oxidation of chloromethane. Theoretical calculations were performed for the decomposition reaction CH3 Cl + M = CH3 + Cl + M and for a set of relevant H‐abstraction reactions (CH3 Cl + R, R = Cl, Ḣ, ȮH, HȮ2, O2, Ö, ĊH3, Ċ2 H3, Ċ2 H5 ; CH4 + Cl, C2 H6 + Cl, C2 H4 + Cl, C2 H2 + Cl). Comparison with previous experimental or theoretical determinations, when available, proved the appropriateness of the adopted protocols and the accuracy of the calculated rate constants. Previously developed subsets for CH3 Cl and HCl/Cl2 were updated with the theoretical rate constants and combined with the CRECK C1 –C3 mechanism, yielding a kinetic mechanism consisting of 143 species and 2347 reactions. The validation was performed through comparison with all the pyrolysis and oxidation measurements available for pure CH3 Cl and its mixtures with CH4, H2, and CO/H2 O. The kinetic discussion highlights the role of key reaction steps that have been theoretically investigated in this work and in previous efforts and sheds light on additional reaction pathways needing better assessments.